Managing the Transformation of Qur’anic Studies: Research Management, Thematic Diversification, and Epistemological Change in Indonesian Islamic Higher Education - Kusnadi; Ahmad Soleh Sakni; Bukhori Abdussomad; Mubaidi Sulaeman; Eko Zulfikar; Deddy Ilyas (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The development of Qur’anic Studies in Islamic higher education has increasingly expanded from classical tafsir toward thematic, contextual, and Living Qur’an approaches. However, the extent to which this thematic diversification is accompanied by methodological and epistemological transformation remains underexplored. This study analyzes the development and management of Qur’anic Studies research at UIN Raden Intan Lampung and UIN Raden Fatah Palembang through Amin Abdullah’s integrative-interconnected perspective. The study employs a qualitative design combined with bibliometric and descriptive-analytical approaches, analyzing undergraduate thesis patterns, publication trends, and keyword networks. The findings reveal two institutional orientations. UIN Raden Intan Lampung tends to develop analytical and multidisciplinary research addressing religious moderation, national ethics, and public health. In contrast, UIN Raden Fatah Palembang demonstrates a stronger orientation toward phenomenological and community-based Living Qur’an studies. Both institutions have diversified research themes beyond classical tafsir, expanding Qur’anic Studies toward social practices and contemporary issues. However, the analysis identifies a gap between thematic diversification and methodological transformation: descriptive research remains prevalent, while critical reflection, epistemological comparison, interdisciplinary integration, international collaboration, and global publication remain limited. From Amin Abdullah’s perspective, this indicates a partial transformation of Qur’anic Studies. The study contributes by identifying a pattern in which thematic diversification develops faster than epistemological and methodological transformation, suggesting the need for stronger connections among Qur’anic texts, Islamic intellectual traditions, academic disciplines, social realities, and institutional research ecosystems.